Melanocytoma of the ciliary body misdiagnosed as iridodialysis - Kim, Moosang (Dove Medical Press, 2014)
A 62-year-old female presented to our institution with dimness of vision in her right eye. On examination, her best corrected visual acuity was 20/100 in the right eye. The intraocular pressures were 14 mmHg in both eyes. Slit-lamp examination revealed nuclear sclerotic cataracts bilaterally and iridodialysis in her right eye. Seven days after the first visit, cataract surgery was performed without any complications. One year later, she presented to our institution with acute visual loss and ocular pain in the right eye. Best corrected visual acuity of the right eye was light perception and the intraocular pressure was 44 mmHg. Slit-lamp examination revealed a ciliary body mass with widespread pigment dispersion in the anterior segment. Due to no useful vision and uncontrolled pain, enucleation of the right eye was performed. Histopathologic examination revealed a melanocytoma of the ciliary body.